LAYANAN KONSELING INDIVIDU DALAM MENGATASI CONDUCT DISORDER PADA REMAJA (STUDI KASUS PADA KLIEN “H”) - Fajar Romadhon (CV. ADIBA AISHA AMIRA, 2023)
Conduct disorder can make individuals like to intimidate others, like to fight, use weapons, destroy their own and other people's belongings, like to run away from home, skip school, steal and commit physical violence to other people or animals. In this study, the researcher aims to find out the description of conduct disorder in client